Uso de corticoides y evolución de pacientes COVID-19 en un hospital nivel III de la amazonía peruana, 2020 - Tobler Gómez, Liz Estefany (2022)
Since the first cases of the new coronavirus (SARS – Cov2 virus) were reported in 2019, this pathology has become a major global health problem. The purpose of the study is to determine the relationship between the use of corticosteroids and the evolution of COVID-19 patients in a level III hospital in the peruvian amazon between March and June 2020. A retrospective observational study was carried out based on the documentary review of 272 patients diagnosed with coronavirus infection, using the WHO COVID-19 case registration form. Univariate and bivariate analysis was performed using Spearman's Rho test to determine correlation. The study showed that the use of corticosteroid therapy before and during hospitalization was associated with almost a 4-fold increased risk of complications, a 3.2-fold increased risk of anemia, a 5-fold increased risk of superimposed pneumonia, and a 4-fold increased risk of ARDS in confirmed cases. In addition, high-dose corticosteroid therapy generated a higher risk of hospital readmission, mortality, and complications such as anemia, superimposed pneumonia, and ARDS. It was determined that its use generated a 2.7-fold risk of presenting some complication, a 3.6-fold increased risk of anemia, a 2-fold increased risk of superimposed pneumonia, and a 2.76-fold increased risk of ARDS in patients with confirmed coronavirus infection.